COMT gene locus: new functional variants. Issue 10 (October 2015) - Meloto, Carolina B.; Segall, Samantha K.; Smith, Shad; Parisien, Marc; Shabalina, Svetlana A.; Rizzatti-Barbosa, Célia M.; Gauthier, Josée; Tsao, Douglas; Convertino, Marino; Piltonen, Marjo H.; Slade, Gary Dmitri; Fillingim, Roger B.; et al.
Abstract : Abstract: Catechol- O -methyltransferase (COMT) metabolizes catecholaminergic neurotransmitters. Numerous studies have linked COMT to pivotal brain functions such as mood, cognition, response to stress, and pain. Both nociception and risk of clinical pain have been associated with COMT genetic variants, and this association was shown to be mediated through adrenergic pathways. Here, we show that association studies between COMT polymorphic markers and pain phenotypes in 2 independent cohorts identified a functional marker, rs165774, situated in the 3′ untranslated region of a newfound splice variant, (a)-COMT. Sequence comparisons showed that the (a)-COMT transcript is highly conserved in primates, and deep sequencing data demonstrated that (a)-COMT is expressed across several human tissues, including the brain. In silico analyses showed that the (a)-COMT enzyme features a distinct C-terminus structure, capable of stabilizing substrates in its active site. In vitro experiments demonstrated not only that (a)-COMT is catalytically active but also that it displays unique substrate specificity, exhibiting enzymatic activity with dopamine but not epinephrine. They also established that the pain-protective A allele of rs165774 coincides with lower COMT activity, suggesting contribution to decreased pain sensitivity through increased dopaminergic rather than decreased adrenergic tone, characteristic of reference isoforms. Our results provide evidence for an essential role of the (a)-COMT isoform in nociceptive signaling and suggest that genetic variations in (a)-COMT isoforms may contribute to individual variability in pain phenotypes. Abstract : Supplemental Digital Content is Available in the Text.A catechol- O -methyltransferase genetic marker of pain led to the discovery of an alternative enzyme that acts through dopamine rather than epinephrine, characteristic of reference catechol- O -methyltransferase.